Impacts of migration on households in the Dry Zone, Myanmar - TEERAWICHITCHAINAN, Bussarawan Puk (Institutional Knowledge at Singapore Management University, 2017)
The study analyzes data from the 2017 Dry Zone Migration Impact Survey to examine the impacts of migration on households in migration‐source areas (Mandalay and Magway Regions). The report describes characteristics and patterns of migration and examines effects on material wellbeing and livelihoods experienced by migrant‐sending households, including needs of dependent children, disabled and elderly household members. Based on the empirical findings, the report also discusses how policy and support can be enhanced to increase the positive impacts of migration on migrant‐sending households and to address its negative consequences.